2009
DOI: 10.1007/s00284-009-9493-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus shivajii sp. nov.: A Novel Basidiomycetous Yeast Isolated from Biogas Reactor

Abstract: Five yeast morphotypes were isolated from biogas reactors at North Wyke Research, Okehampton, UK. Out of the five morphotypes, four were identified as known species. In contrast, the fifth morphotype strain, Bio10(T), was found to differ from Bullera dendrophila and Kwoniella mangroviensis, its closest phylogenetic neighbours, by 2.6-2.9% with respect to the nucleotide sequence of the D1/D2 domain of the 26S rRNA gene and by 5.6-6.2% with respect to the internal transcribed spacer 1 (ITS1)-5.8S rRNA gene-ITS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Earlier studies by Ravella et al . () showed that a laboratory‐scale biogas reactor is an appropriate habitat for fungi as viable strains of different yeasts could be isolated under aerobic conditions. The origin of the fungal cells found in the present study remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by Ravella et al . () showed that a laboratory‐scale biogas reactor is an appropriate habitat for fungi as viable strains of different yeasts could be isolated under aerobic conditions. The origin of the fungal cells found in the present study remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the eukaryotic community dominated by fungi did not change, and the fungi remained present over the time period of 1 year [19]. Also, Ravella et al [33] demonstrated that a laboratory biogas reactor is a suitable habitat for fungi, and the authors were able to isolate different viable fungal strains.…”
Section: Role Of Fungi In Biogas Reactorsmentioning
confidence: 91%
“…We thus selected genetically distinct strains or those from different samples or geographic origins for the MLST analysis. We also included in the MLST analysis the taxa studied by Findley et al (14) but added two recently described species in the Kwoniella clade: Cryptococcus pinus (30), including the type strain as well as a recent isolate from insect larvae in Belgium (MUCL 53261; see Table S1 in the supplemental material), and Cryptococcus shivajii (31). Tremella mesenterica served as an outgroup for the analysis.…”
Section: Mating Experimentsmentioning
confidence: 99%